A Layered Photo-Anode Prepared Using TiO2 Nanocrystals with Different Sizes for Enhanced Light-Trapping in Quantum Dots-Sensitized Solar Cells. (1st January 2019) - Deng, Jianping; Wang, Minqiang; Fang, Junfei; Li, Le; Feng, Rong; Yang, Zhi; Song, Xiaohui
Abstract : Using TiO2 nanocrystals (NCs) with diameters of 20 nm (T20), 40 nm (T40) and 60 nm (T60) as starting materials, three TiO2  photo-anodes were constructed on FTO glass. Meanwhile, a triple-layered photo-anode was prepared by depositing the T20, the T40, and the T60 layer by layer on FTO glass (T60/T40/T20/FTO/glass). These four kinds of photo-anodes were sensitized with CdZn0.02 S0.08 Se0.92 QDs by successive ionic layer adsorption and reaction (SILAR). Based on these photo-anodes, four quantum dot-sensitized solar cells (QDSSCs) were finally obtained. The results indicated that the highest efficiency of 3.95% was obtained in the QDSSC with the triple-layered photo-anode. The short-circuit photocurrent density (Jsc ) of the QDSSC with the triple-layered photo-anode was 1.25, 1.21 and 1.13-fold higher than that of the QDSSCs with T20-, T40- and T60-based photo-anode, respectively. Moreover, with the increase of the average size of the TiO2  NCs from 20 to 60 nm, the Jsc increased from 13.8 to 15.24 mA·cm −2 . The optical properties, crystal structure and morphologies of the bare TiO2 films and the CdZn0.02 S0.08 Se0.92  sensitized TiO2  photo-anodes were characterized by UV-Vis spectroscopy, XRD and SEM. The incident photon-to-electron conversion efficiency, the open circuit voltage decay and the electrochemical impedance spectroscopy of the QDSSCs were measured and discussed, so as to clarify the underlying mechanism of the property enhancement.